The relationship between HRD strategies, career success and employee retention - Cheong, Chew Yee (2015)
The retention of engineers is critical for a developing country like Malaysia, since engineer’s contributions are considered vital to the growth of Malaysia. Turnover especially among skilled and technical employees are a major concern for many organizations. This study investigates the relationship between human resource development (HRD) strategies and employees’ career success as well as employees’ intention to continue working with their employing organization. The aim for present study is firstly, to determine the level of implementation for HRD strategies, career success and intention to stay in the company; secondly, to examine the relationship between these three variables - HRD strategies, employees’ career success and intention to stay in the company; thirdly, to examine the most important HRD strategies among employees’ career success or intention to stay in the company. Using quantitative design research, data was collected through survey questionnaire from a sample of 61 respondents. The analysis was carried out using descriptive and inferential statistics. Three of the dimensions of HRD strategies, namely training and development, learning, and career development were well implemented in the company. However, engineers perceived a moderate level of career success. Moreover, engineers also perceived a moderate level of intention to stay. In general, all the three HRD strategies were having positive and significant relationship with engineers’ career success. There is also a positive and significant relationship between learning and career development, and engineers’ intention to stay. Furthermore, there is a positive and significant relationship between engineers’ career success and their intention to stay. Career development has the strongest influence towards engineers’ career success, whilst learning has the strongest influence towards engineers’ intention to stay.